Analisis Strategi Marketing Mix (4p) Dalam Meningkatkan Volume Penjualan Pada Perusahaan Jasa Periklanan Bigevo Di Jakarta Selatan Tahun 2019 - Rina Ayu Vildayanti (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2020)
In the field of marketing, entrepreneurs need to have strategy in marketing their products. One of marketing strategy that is able to support the marketing of advertising services products to create customer loyalty is the strategic use of marketing mix which includes product, price, place and promotion. If consumers get satisfaction with products for sale, then they will be loyal. If realized customer loyalty, it will impact on increased sales. The purposes of this research are to analyze marketing mix strategy in increasing sales volume at advertising service company BigEvo on South Jakarta in 2019. Methodology of research took a qualitative data obtained from documentation, literature review and interviews to president director of PT. Orange Global as advertising services BigEvo which is further associated with the theories developed in accordance with the research conducted. Data analysis techniques used in this research is descriptive qualitative where more qualitative research is aimed at the establishment of substantive theory based on concepts arising from empirical data. Descriptive qualitative method used to examine more deeply about strategy of product, price, place, and promotion in increasing sales volume at advertising service company BigEvo. The results of this study prove that marketing mix were able to increase sales volume and put BigEvo as advertising services company in Jakarta.Keywords: Advertising Services, Marketing Mix, Sales Volume.